(3TQM bUjOg GdfGHZI GdPHjGfi (B( (3GdOGdjg (B)s - (3dCHi GdMSf Ydj Hf CMeO Hf eMeOs; (3RjGO Hf eYGhjI Hf VHGH GdPHjGfqj GdZWaGfqj GdeVQj, CHh CeGeI (B((3GdnqfGHnZI GdoqPrHnjGfj(B)s ((3eMeO Hf CHj GdaVd GdUGjZi GdHjgbi s)
(3ChdgG (B:s
(3jGOGQ ejI HGdYdjGA aGdSfO CbhJ aWGd Ydi SGda GdCHO s
(3BNQgG (B:s
(3gPG GdPi PcQJ YPQi aEf de jfaYfi JMjQJ hde CgJO dhLg JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJH GdTYQ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs